(untitled) (SCIENCE TIME JOURNAL, 2026)
Culturally responsive teaching (CRT) has emerged as a critical pedagogical approach in English as a Foreign Language (EFL) and English as a Second Language (ESL) classrooms, where learners come from diverse linguistic and cultural backgrounds. This article examines the theoretical foundations, practical strategies, and impacts of CRT on language acquisition and learner engagement. The study highlights how integrating students’ cultural identities into instructional practices enhances motivation, inclusivity, and academic achievement. Drawing on contemporary research, the article analyzes the role of teachers in fostering culturally sustaining environments and proposes recommendations for effective implementation in multilingual settings